This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The thing we have to do here is to solve it for integration by parts.
The Equation for integration by parts goes like this:
∫ 0 π f ( x ) g ′ ( x ) d x = f ( x ) g ( x ) − ∫ 0 π f ′ ( x ) g ( x ) d x
So we have to apply this rule where:
f ( x ) = x
… and …
g ( x ) = ( sin x + cos x )
Because of this we can say that the integral is equivalent to the following function:
-It's important to remember that the pi and the 0 represent radian values in terms of the trigonometric functions.
∫ 0 π x ( sin x + cos x ) d x = x ( sin x − cos x ) − ∫ 0 π ( sin x + cos x ) d x
If you use basic integration you'll find that:
∫ 0 π ( sin x + cos x ) d x = 2
So:
= x sin x − x cos x − 2
There for if we take the original integral we have to find the following:
= x sin x − x cos x − 2 … as an integral from 0 to π radians
So we have the following equation:
= [ ( π ) sin ( π ) − ( π ) cos ( π ) ] − [ ( 0 ) sin ( 0 ) − ( 0 ) cos ( 0 ) ] − 2
= − π cos ( π ) − 2
= − π ( − 1 ) − 2
= π − 2
= 3 . 1 4 1 5 9 2 6 − 2
= 1 . 1 4 1 5 9 2 6
The answer thus would be : 1 . 1 4 1 5 9 2 6
This is how you can work out the answer.